Pengaruh Citra Perusahaan dan Kualitas Pelayanan Terhadap Kepuasan Anggota Pada Koperasi Bayu Sudana di Tabanan - Prananda Kusuma, I Gede Agus; Putu Kawiana, I Gede; Adisti Abiyoga Wulandari, Ni Luh (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the influence of corporate image on the satisfaction of members of the Bayu Sudana Cooperative in Tabanan, to determine the effect of service quality on customer satisfaction, and to determine the influence of corporate image and service quality on the satisfaction of members of the Bayu Sudana Cooperative in Tabanan. The number of samples in this study was 78 people. The data collection method was carried out by interviewing, observing, and distributing questionnaires to respondents. The data analysis techniques used are Classical Assumption Test, Multiple Linear Regression, Determination Analysis, T-Test, and F-Test. The results obtained in this study are: 1) the company’s image has a positive and significant effect on member satisfaction with a calculated t value (2,040) > t table (1,990) and a sig value of 0.045<0.05. 2) Service quality has a positive and significant effect on member satisfaction with a calculated t value (3,039) > t table (1,990) and a sig value of 0.003 <0.05. 3) Company image and service quality have a positive and significant effect on member satisfaction with F calculated values (24,885) > F table (3.11) and GIS values 0.000<0.05. Suggestions that can be given so that the company adds relationships or open sponsors to support activities in the cooperative, improve responsive services for members and provide important information for all members of the Bayu Sudana Tabanan cooperative.